Psychometric validation of the Weiss Functional Impairment Rating Scale-Parent Report Form in children and adolescents with attention-deficit/hyperactivity disorder - Gajria, Kavita; Dittmann, Ralf (Health and quality of life outcomes, 2015)
Measurement properties of the Weiss Functional Impairment Rating Scale-Parent Report Form (WFIRS-P), which assesses attention-deficit/hyperactivity disorder (ADHD)-related functional impairment in children/adolescents (6-17 years), were examined.